Football is medicine: It is time for patients to play! - Krustrup, P.; Krustrup, B. R. (British Journal of Sports Medicine, 2018)
In 2006, the recognised Nordic exercise physiologists Professors Pedersen and Saltin provided powerful evidence that exercise was an effective therapy in chronic disease—they emphasised exercise as a cornerstone in the prevention and non-pharmacological treatment of lifestyle diseases.1 Shortly after, American College of Sports Medicine (ACSM)`s president Dr Sallis delivered his well-documented and strong statement that `exercise is medicine and physicians need to prescribe it!`.2 These statements, and the research on which they are based, have influenced health authorities and governments around the globe to include exercise recommendations in the prevention and treatment of chronic diseases. Prominent worldwide exercise guidelines, including those from the WHO and ACSM, encourage sedentary individuals and patients to engage in exercise activities like brisk walking, jogging, cycling and fitness centre training. However, within physical activity guidelines, less emphasis has been placed on the health benefits of sporting activities.